Пасіонарність етносу як ключовий момент геогенетичної зони Глухівщини - Мироненко, А.М. (Сіверщина в історії України, 2024)
Стаття присвячена виявленню та обґрунтуванню причин наявності окремої локації з підвищеним культурним потенціалом на території Глухівщини. У роботі культурний регіон Глухівщини розглядається з точки зору понять «геогенетична зона» та «соціолокус», уведених у науковий обіг музикознавицею Валентиною Кузик. Причини наявності саме такої геозони на Глухівщині обґрунтовуються за допомогою теорії пасіонарності вченого Льва Гумільова. Саме завдяки їй пояснюється сплеск великої кількості визначних особистостей, які народилися та творили на теренах Глухівщини упродовж XVII – на початку ХХ ст., що відповідає акматичній фазі етногенезу. Крім того, наводиться гіпотеза щодо ймовірного існування окремого субетносу на території Гетьманщини – козацтва. На наш погляд, теорія, незважаючи на деяку емпіристичність у певних питаннях, є логічною, адже її ефективність доведена аналізом етногенезу відомих етносів Землі. The article is devoted to identifying and justifying the reasons for the existence of a separate location with increased cultural potential in the territory of Hlukhiv region. In the work, the cultural region of Hlukhiv region is considered from the point of view of the concepts «geogenetic zone» and «sociolocus», introduced into scientific circulation by musicologist Valentina Kuzyk. The reasons for the existence of such a geozone in the Hlukhiv region are substantiated with the help of the theory of passion of the scientist Lev Gumilyov. It is thanks to her that the surge of a large number of outstanding personalities who were born and created on the territory of Hlukhiv region during the 17th and early 20th centuries, which corresponds to the akmat phase of ethnogenesis, is explained. In addition, a hypothesis is given regarding the probable existence of a separate sub-ethnicity on the territory of the Hetmanate - the Cossacks. In our opinion, the theory, despite some empiricism in certain issues, is logical, because its effectiveness is proven by the analysis of the ethnogenesis of the known ethnic groups of the Earth.